XGASS: The impact of photometric bulges on the scatter of HI scaling relations. Issue 3 (7th October 2019) - Cook, Robin H W; Cortese, Luca; Catinella, Barbara; Robotham, Aaron
ABSTRACT: We present a structural decomposition analysis of the galaxies in the extended GALEX Arecibo SDSS Survey (xGASS) using ( gri ) images from the Sloan Digital Sky Survey. Utilizing the 2D Bayesian light profile fitting code ProFit, we fit single- and double-component models taking advantage of a robust Markov chain Monte Carlo optimization algorithm in which we assume a Sérsic profile for single-component models and a combination of a Sérsic bulge and near -exponential disc (0.5 ≤ n ≤ 1.5) for double-component models. We investigate the effect of bulges on the atomic hydrogen (H i ) content in galaxies by revisiting the H i -to-stellar mass scaling relations with the bulge-to-total ratio measured in the ProFit decompositions. We show that, at both fixed total and disc stellar mass, more bulge-dominated galaxies have systematically lower H i masses, implying that bulge-dominated galaxies with large H i reservoirs are rare in the local Universe. We see similar trends when separating galaxies by a bulge-to-total ratio based either on luminosity or stellar mass, however, the trends are more evident with luminosity. Importantly, when controlling for both stellar mass and star formation rate, the separation of atomic gas content reduces to within 0.3 dex between galaxies of different bulge-to-total ratios. Our findings suggest that the presence of a photometric bulge has little effect on the global H i gas reservoirs of local galaxies.